Peran Esensial Brand Image Dan Harga Dalam Membentuk Keputusan Pembelian Konsumen Elzatta di Kota Depok - Trinasih; Nayla Alifiandra; Diana Anggraeni; Dita Chairunnisa; Muhammad Abdullah (MOTIVASI, 2025)
Purpose - This study aims to examine the influence of brand image and price on purchasing decisions for the Elzatta hijab brand in Depok City. Design/methodology - This research adopts a quantitative associative approach to identify the causal relationship between brand image, price, and purchasing decisions of the Elzatta hijab brand in Depok City. Primary data were collected through a questionnaire distributed to 96 Elzatta hijab buyers in Depok. The sample was obtained using non-probability purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS version 25. Findings - The results indicate that both brand image and price, either partially or simultaneously, significantly affect purchasing decisions. The relationship between the independent and dependent variables is very strong, with 74.90% of purchasing decisions for Elzatta hijabs in Depok being influenced by brand image and price.